Epidemiological and histopathological aspects of primary cutaneous melanoma in residents of Joinville, 2003-2014 - Raquel Bissacotti Steglich; Karina Munhoz de Paula Alves Coelho; Silvana Cardoso; Maria Helena da Costa Naumann Gaertner; Tania Ferreira Cestari; Selma Cristina Franco (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: The worldwide incidence of cutaneous melanoma (CM) has been continuously increasing over the last decades. Primary and secondary prevention, with attention to risk factors and early diagnosis, remain the cornerstone for reducing the burden of cutaneous melanoma. Detailed information with respect to clinical and pathological data on cutaneous melanoma is scarce in Brazil. Objective: The purpose of our study was to analyze epidemiological and pathological characteristics of primary cutaneous melanoma in Joinville, southern Brazil. Methods: Observational, cross-sectional, retrospective study in which 893 reports of primary cutaneous melanoma from the local population were analyzed in the period 2003-2014. The study was approved by the local Ethics and Research Committee. Results: We observed a female predominance of cutaneous melanoma (56.3%). The age standardized incidence rate of primary cutaneous melanoma for the world population in the period 2003-06 was 11.8 per 100,000 population (CI 95%, 10.3-13.4), and 17.5 (CI 95%, 15.7-19.3) in 2011-14, revealing a significant increase of 48.3% (p < 0,05). Six and a half percent of patients had multiple cutaneous melanomas (mean 2.2 years and a maximum of 10.0 years between diagnoses). We observed significant differences between the location head/neck and cutaneous melanoma in situ, lower limb with Breslow depth S III and upper limb with Breslow depth S I. The comparison of the characteristics of cutaneous melanoma in the elderly and non-elderly (< 60 years old) showed significant differences with respect to all the variables studied. Study limitations: Using secondary data source. Conclusion: Joinville has high incidence coefficients for Brazilian standards, showing an increase in the incidence of cutaneous melanoma.